Pemberdayaan Masyarakat Melalui Pengembangan “Soft Skill Pembuatan Gula Merah” Dalam Upaya Peningkatan Pendapatan Keluarga Di Desa Paya Lombang Kabupaten Serdang Bedagai - Sinaga, Eka Mayastika; Fitrianingsih, Fitrianingsih; Nainggolan, Benhart; Rusmewahni, Rusmewahni; Murniati, Neni (Community Service Progress, 2024)
This community service activity emphasizes empowering village communities through developing soft skills for making brown sugar in an effort to increase family income in Paya Lombang Village, Serdang Bedagai Regency. The aim of this activity is to empower the community by providing skills that can increase family income thereby increasing welfare. The aim of this Community Service Activity is to develop MSMEs (Micro, Small and Medium Enterprises) and creative industries in the community of Paya Lombang Village, Serdang Bedagai Regency. Especially in the village's superior product, namely brown sugar products, through the development of soft skills in making brown sugar.